Empowerment of Light Exposure and Nutrient Composition to Photobioreactor of Algae Performance - O. H. Cahyonugroho; A. U. Farahdiba; A. A. H. Putro (Future Science)
Air pollution, such as CO2 gasoeus, is one of the environmental issue in the world, instead of other gasoeus pollutant. Microalgae has been known as an micoplant that could adsorb CO in order to reduce CO2 concentration. Microalgae fixation reachs 10-15 times more efficient compared with the other microplants. Microalgae growth depends on many factrs, such as light, temeprature, nutrition, pH, salinity, CO2, techinal aspect, bitic factors, etc. The objective of this research is to know the correlation of light exposure and nutrient composition to the performance of algae photobioreactor. The experimental was setup in photobioreactor of algae under light intensity 1000-2000 lux, light time exposure (hours): 6, 12, 18, 24, and nitrogen to phosphor nutrient composition 25:75; 75:25; 50:50; 100:0; 0:100. The results shown light exposure affect the production of chlorophyll-a, biomass productivity, and CO2 absorption, which was presented by p-value <0.005. The opposite result indicated that nutrient composition has insignificantly effect to the photobioreactor of algae performance with p-value > 0,005.